Memahami Hindutva dan Implikasi bagi Toleransi di India - Paulus Tegar Setiadi (Sekolah Tinggi Teologia dan Filsafat Widya Sasana, 2026)
This article discusses the Hindutva issue that threatens pluralism and interfaith dialogue in India. Hindutva is a Hindu ideology in India proposed by Vinayak Damodar Savarkar. The purpose of this research is to critically analyze the biography, intellectual background, and how Sarvarkar expresses his thoughts. Hindutva is exclusive and legitimizes the practice of violence. The method used in this article is literature study with a focus on writings discussing Hindutva. The results show that Hindutva is an exclusive Indian nationalism with religions and cultures originating from outside Indian soil. This nationalist spirit has the potential to trigger radicalism similar to fascism patterns. This analysis emphasizes the need for religious moderation to avoid destructive radicalism that undermines interfaith dialogue.